Central retinal artery occlusion – detection score - Casagrande, Maria; Steinhorst, Nils Alexander; Dippel, Susanne Kathrin; Kück, Fabian; Grohmann, Carsten; Spitzer, Martin S.; Poli, Sven; Feltgen, Nicolas; Schultheiss, Maximilian (Frontiers in Medicine, 2023)
Purpose: To investigate the sensitivity and specificity of central retinal artery occlusion (CRAO)-Detection Score diagnosing CRAO via questionnaire and without fundoscopy. Methods: This prospective study enrolled 176 emergency patients suffering from acute visual loss, of whom 38 were suffering from CRAO. Before conducting any examination, we administered our questionnaire containing six questions, followed by a thorough ophthalmologic examination making the diagnosis. Statistical analysis involved a LASSO penalised multivariate logistic regression model. Results: Our receiver operating characteristic (ROC) analysis based on a LASSO penalized multivariate logistic regression model showed an area under the curve (AUC) of 0.9 – 3 out of 6 questions were selected by LASSO. Interestingly, the unweighted ROC analysis of only 2 questions (Short CRAO-Detection Score) yielded similar results with an AUC of 0.88. The short CRAO-Detection Score of 2 yielded 14 % (4/28) false positive patients. Conclusion: This prospective study demonstrates that a high percentage of CRAO-patients are detectable with a questionnaire. The CRAO-Detection Score might be used to triage patients suffering acute visual loss, which is important as intravenous fibrinolysis seem to be time-dependent effective.